Frequency of significant fibrosis in various chronic liver diseases: an evaluation with Transient Elastography (TE) - shahrani, shahreedhan; balakrishnan, preetica mayuri; ravi, koshni; singh, sandeep; chee, sher wye; zulkeflie, saiful hasyim; zhuang, ng ying; lee, wai kin; amin, Mohamed; sooi, choong yeong; CK, vikneshwaran; Nik Muhamad Affendi, Nik Arsyad; et al. (2022)
INTRODUCTION: Liver biopsy has long been the gold standard to evaluate liver fibrosis. TE was developed as a non- invasive method to assess liver fibrosis by measuring liver stiffness using shear wave velocity. Many studies have proven its’ effectiveness as a method for evaluating liver fibrosis.1-2 The use of TE in UMMC began in 2013. OBJECTIVE: To determine the frequency and aetiology of liver fibrosis and cirrhosis in our local population METHOD: This was a retrospective study conducted at UMMC. Inclusion criteria was all patients who had TE performed from 1 January 2013 to 31 December 2021. Their demographics, clinical characteristics and TE findings were charted. RESULTS: A total of 3066 patients were included, in which 51.7% were males and 48.3% were females. The median CAP value was 271 dB/m. The median E value was 6.5kPa. 11.2% and 11.3% of patients had significant fibrosis (10.1-14.9kPa) and cirrhosis(≥15kPa) respectively. Non-alcoholic fatty liver disease (NAFLD) was noted to be the most common aetiology for fibrosis (32.8%), followed by chronic hepatitis B (CHB) at 25.2%, chronic hepatitis C (CHC) at 6.7% and alcoholic liver disease (ALD) with 1.3%. This finding was also found to be similar in the cirrhosis group (NAFLD 32.5%, CHB 17.2%, CHC 11.9% and ALD 1.4%). 219